Factors Affecting Investment Decisions of Individuals: A Comparative Study Between Developed and Emerging Markets (The Case of Jordan) - Al-Rafayah, Ahmed Abdullah (Journal of Ecohumanism, 2024)
This study aimed to analyze the factors influencing individuals’ investment decisions in Jordan, comparing emerging markets (such as Jordan) and developed markets (such as Dubai). The sample included 100 individual investors (50 from Jordan and 50 from Dubai), and a 30-item questionnaire covering economic, psychological, social, and technical factors was used. The results showed that economic factors such as inflation and growth significantly influence investment decisions in both markets, but without significant statistical differences, as the T-statistic value for economic factors was 0.8665 and the P-value was 0.3883. On the other hand, psychological factors were more influential in developed markets, as the T-Statistic showed a value of -4.3778 and the P-value was 0.00003, indicating that Dubai investors bear more risks than Jordan. Technical factors significantly impacted developed markets, as the F-statistic value was 9.623 and the P-value was 0.0025. In contrast, the study showed that investors in emerging markets face more significant challenges compared to developed markets, with a T-Statistic of 6.6154 and a P-Value of 0.0000000019. The study recommends increasing government support to enhance political and economic stability in emerging markets to mitigate investor challenges. It also recommends enhancing the use of technology in investing in emerging markets, and improving financial education to encourage informed risk-taking. In addition, it is suggested that regulators in developed markets adopt strategies that support greater transparency and clarity of investment opportunities to facilitate decision-making.